Leptin is Associated with the Tri-Ponderal Mass Index in Children: A Cross-Sectional Study - Empringham, Brianna (Adolesc Health Med Ther, 2021)
BACKGROUND: Obesity is characterized by the disproportionate expansion of the fat mass and is most commonly diagnosed using the Body Mass Index (BMI) z-score or percentile in children. However, these measures associate poorly with the fat mass. This is important, as adiposity is a more robust predictor of cardiometabolic risk than BMI-based measures, but there are limited clinical measures of adiposity in children. A new measure, the Tri-ponderal Mass Index (TMI, kg/m(3)) has recently demonstrated robust prediction of adiposity in children. The aim of this study is to explore the association of leptin, a validated biomarker of the fat mass, with TMI. METHODS: One hundred and eight children and adolescents were included in this cross-sectional study. Height and weight were used to calculate TMI. Plasma leptin was measured using ELISA. Multivariable regression analysis was applied to determine the predictors of TMI. RESULTS: The age range of participants included in this study was 8.00–16.90 years (female n=48, 44%). Leptin correlated with BMI percentile (r=0.64, p-value <0.0001) and TMI (r=0.71, p-value <0.0001). The multivariable regression analysis revealed that BMI percentile (Estimated Beta-coefficient 0.002, 95% CI 0.002–0.003, p-value <0.0001) and Leptin (Estimated Beta-coefficient 0.05, 95% CI 0.02–0.07, p-value 0.013) were associated with TMI. CONCLUSION: Leptin is associated with TMI in healthy children. The TMI is a feasible clinical measure of adiposity that may be used to stratify children and adolescents for further assessments and interventions to manage and attempt to prevent cardiometabolic comorbidities.